Exploring the impact of e-WOM on customer purchasing intention and co-creation of adults who use Taobao - Feng, Mengyi (2018)
The rise of multiple media channels has created numerous opportunities for electronic wordof-mouth communications, and an increasing number of customers prefer to use virtual communities, forums, and consumer review sites to share online shopping experiences with other users. Therefore, understanding the actual effects of electronic word-of-mouth communications on customer purchasing intention and value co-creation seems to be equally important for theoretical researchers and practical marketers. This research-based study seeks to explore the extent to which customer purchasing intention and co-creation behaviors would be affected by e-WOM quality, quantity and credibility on the Chinese most popular online shopping website Taobao. Also, the study investigates the influence of gender differences posed on purchase intention, trying to examine whether female customers and male customers would make different purchasing decisions on the Taobao platform.